Akibat Hukum Harta Bersama Perkawinan Dalam Pewarisan Di Indonesia Analisis Komparatif Hukum Islam Dan Hukum Adat - Muthmainnah Muthmainnah; Fattah Setiawan Santoso (Universitas Cokroaminoto Yogyakarta, 2019)
this paper examines the inheritance relating to joint property in marriage and recipients in the form of a comparison between Islamic law and customary law normatively. Customary law here is related to other customs and customs adopted by the Muslim community. Islamic law and customary law of Indonesian Muslim tribes have in common especially in terms of inheritance barriers. The potential for equality in the distribution of inheritance, including shared and inherited assets, is also very prominent.